2012
DOI: 10.1111/j.1477-2574.2011.00378.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of 18FDG PET/CT in the management of colorectal liver metastases

Abstract: The addition of PET/CT led to management changes in over one-third of patients but there was no correlation between alterations in staging or management and the Fong clinical risk score; suggesting that PET/CT should be utilized, where available, in the pre-operative staging of CLM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…The false negative rate was 2% and comparable with other contemporaneous studies. 15,16 A systematic review in 2005 by Weiring et al looked at 32 separate studies and showed FDG PET to have a higher sensitivity than CT for the detection of extrahepatic metastasis (91.5% vs 60.9%). 12 Most of the studies reviewed focused on the clinical impact or change in management due to the FDG PET, with change in 20-32% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The false negative rate was 2% and comparable with other contemporaneous studies. 15,16 A systematic review in 2005 by Weiring et al looked at 32 separate studies and showed FDG PET to have a higher sensitivity than CT for the detection of extrahepatic metastasis (91.5% vs 60.9%). 12 Most of the studies reviewed focused on the clinical impact or change in management due to the FDG PET, with change in 20-32% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Engledow et al looked at the use of the Fong clinical risk score 22 in the context of PET-CT in CLM. 16 They found that PET-CT changed management in 34% of patients and that there was a trend towards PET-CT being more influential in patients categorised as low risk by Fong criteria (44%) in comparison with the high risk patients (14%) although this failed to reach statistical significance. The study by Engledow et al raises the question of how patients might best be selected for PET-CT.…”
Section: A B Cmentioning
confidence: 98%
See 1 more Smart Citation
“…Engledow et al [23] evaluated the yield of the FDG-PET in an attempt to stratify the use of the FDG-PET in patients with CRLM depending on CRS. The influence on management failed to reach statistical significance between low- and high-CRS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The influence on management failed to reach statistical significance between low- and high-CRS patients. Based on this series, the Fong et al [10] CRS should not be used to rationalize the use of PET/CT in those patients being investigated for potential resection of CRLM [23]. Schüssler-Fiorenza et al [22] evaluated whether the CRS correlates with the yield of FDG-PET in patients with CRLM.…”
Section: Discussionmentioning
confidence: 99%